Strengthening Indonesia’s Healthcare Resilience Through the Establishment of Local Medical Device Manufacturing - Yudi Abdillah Sobrizal; Sylviana Maya Damayanti; Subiakto Soekarno (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Indonesia’s healthcare system is still heavily dependent on imported dialyzers, with around 89% of national demand supplied from abroad. This high level of import reliance impacted to the healthcare sector to supply disruptions and ongoing capital outflow, the problems that became particularly apparent during the COVID-19 pandemic. Inline with the number of patients requiring routine dialysis is continue to increase, the demand for dialysis medical devices has also increased. This situation emphasizes the importance of developing local manufacturing facilities to strengthen healthcare resilience in Indonesia. This study assesses the feasibility of establishing a local dialyzer manufacturing facility in Indonesia through a case study of PT. Ichiban Medical Global (pseudonym name). The research uses a case study approach with primary data from internal company sources, including investment, cost, and operational projections, supported by secondary data from government regulations, BPJS Kesehatan, industry associations, and international health organizations. The analysis covers market demand, regulatory support under the Domestic Content Requirement (TKDN) policy, technical and operational readiness, and financial feasibility using capital budgeting methods. The results indicate strong and sustainable market demand supported by BPJS coverage and single-use dialyzer regulation, along with favorable government policies such as TKDN incentives and e-Catalog procurement. Financial analysis shows positive investment outcomes, with a positive Net Present Value, an Internal Rate of Return above the cost of capital, and an acceptable payback period. Overall, the study concludes that local dialyzer manufacturing is financially viable and strategically important for reducing import dependency and strengthening Indonesia’s healthcare system.